Play on the Meaning of Name in Cicero’s Verrines: Some Remarks on Div. Caec. 48–50 - Kučinskienė, Audronė (Hyperboreus, 2019)
Cicero’s use of wordplay with the names of his opponents is well-attested in his speeches, in the Verrines among other works, and has been discussed more than once. Both in the Divinatio in Caecilium and later in the Second Action against Verres Cicero masterfully and inventively uses this type of paronomasia in two ways: he not only exploits the meaning of the name itself (verres ‘boar, hog’), but also creates lusus verborum based on the similarity of words, such as between Verres and everriculum ‘broom’. The passage in Divinatio in Caecilium 48–50, which, as we argue, contains one more pun on the name of the Alienus, lacks more detailed commentary.Having proven Caecilius’ incompetence as prosecutor (Div. Caec. 27–46), Cicero takes a further step by criticizing other potential supporters of this prosecution (subscriptores). One of them, Titus Alienus, receives treatment in two whole paragraphs (Div. Caec. 48–50), which are analyzed in this paper. The main focus of the discussion is the interpretation of the ironic phrase hunc tamen a subselliis, as well as paronomasia based on the meaning of Alienus’ name (ex alienissimis).I argue that the bitterly sarcastic characteristisation of Alienus in Div. Caec. 48–50 demonstrates not only the incompetence of Alienus but that of Caecilius as well: despite his name, Alienus “from the benches” is familiar to the reality of criminal courts in contrast to Caecilius himself. Thus the phrase hunc tamen a subselliis sounds as an ironic compliment, which highlights the lack of competence of Cicero’s main opponent even further, a topic already discussed by the orator in the previous chapters of the speech (Div. Caec. 27–46).